Albani's methodology on the Admissibility of khabar ahad in 'aqidah : an analytical study - Siti Maimunah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, Internatonal Islamic University Malaysia, 2019)
'Aqidah is central pertinent issue in Islam. Among the central points debated among the scholars is whether khabar ahad can be accepted in matters of 'aqidah, or only mutawatir Hadith can be used in this matter. This study explains the stand of one of the most prominent contemporary Hadith scholars, Muhammad Nasir al-Din al-Albani on this issue. It explores the methodology used by Albani in dealing with khabar ahad and analyses whether he has special requirements in dealing and accepting khabar ahad in 'aqidah. This study also examines the similarities of Albani's method compared to the methodology of other scholars. It assesses the interpretational implications of the different opinions regarding this issue. This study relies on library research as well as comparative analyses resulting in several research findings. The study shows that the methods used by Albani in admissibility of khabar ahad in 'aqidah did not contradict the methods of other prominent scholars of Hadith. This work provides a major contribution to the understanding of the reasons why the scholars have different opinions regarding the issue of khabar ahad in 'aqidah and the implications resulting from these differences.